Akt2 siRNA-nanoparticulate system as a new tool to restoration of e-cadherin and eradicate tumor metastic phenotype - Rafael, Diana Fernandes de Sousa 1987- (2017)
Tese de doutoramento, Farmácia (Tecnologia Farmacêutica), Universidade de Lisboa, Faculdade de Farmácia, 2017